A census tract level analysis of urban sprawl's effects on economic mobility in the United States. (August 2021) - Smith, Russell M.; Blizard, Zachary D.
Abstract: Researchers highlight the importance of urban form and sprawling development patterns as determinants of economic mobility in the United States. However, the relationship is complex because sprawl affects other variables too, which themselves may affect upward mobility. This study uses a structural equation model to estimate the direct and indirect effects of urban sprawl, and related components of the built environment, on mobility at the census tract level. The results suggest that compactness has a positive direct effect on mobility, but an overall negative indirect effect on mobility through the tested mediating factors. Hence, there are both positive and negative side-effects associated with compactness in regards to economic mobility. In light of these findings, this paper recommends policies, programs, and procedures for the planning community to aid in alleviating the negative consequences of sprawl on economic mobility, while maintaining the positive ones. Highlights: Urban sprawl directly and indirectly effects upward economic mobility at the census tract level in the United States. The direct effect of compactness on mobility is positive, though the total indirect effect is negative. More compact census tracts have higher rates of upward mobility than more sprawling ones. Indirect effects through social capital, poverty, job access, housing stock, and education quality are negative. Indirect effects through concentrations of non-white minorities and food deserts are positive.